A feketegazdaság (olajkereskedelem és KGST-piac) és vállalkozói Kelet-Magyarországon (Szociológiai Szemle, 2024)
The authors summarise the results of a research, conducted between 1996 and 1998, studying how the phenomenon of black economy (smuggling of oil, CMEA-market) is socially embedded in Eastern Hungary. Studying the problematique of black economy also from the aspect of social history, it is found that the CMEA-market and the smuggling of oil are nothing else but the renewed institutionalisation of the formerly existing ethnic and regional division o f labour, this time adjusted to the requirements of the 90s, in other words, it is a return to the trade relations organised spontaneously on the grass-root level among the peoples of the Carpathian Basin before 1920. It is stressed in relation to the black economy of the 90s that the forms of activity are significant primarily as survival strategies, and that the forms becoming massively employed are due to the lack o f alternative forms of livelihood. The relative lack of state regulation may be traced back to an intention to preserve social peace. Black economy offers resources to investment in the backward northeastern region, stretching over state borders, it creates job opportunities and demand for the losers of systemic change. Thus such a viable development of the area and of the economy, organised from below, is realised which is moved by the losers of transformation, and against which the state has not yet been able to offer alternatives beyond aid given by social policy.